The Technique of Endovascular Intracranial Revascularization - Connors, John J.; Wojak, Joan C.; Hoppe, Blaine H. (Frontiers in Neurology, 2014)
Intracranial atherosclerosis was traditionally believed to carry a risk of stroke of 8% to 22% per annum. The annualized stroke rate in the recent Stenting and Aggressive Medical Management for Preventing Stroke in Intracranial Stenosis trial medical management arm was 12.2%. This trial was halted due to excessive periprocedural events in the stent arm. This stroke rate Is still Unacceptably high and a treatment strategy is still needed. SAMMPRIS has no bearing on angioplasty alone. Angioplasty alone has always been our primary intervention for intracranial atherosclerosis and remains so to this day due to its relative simplicity, low complication rate, and efficacy. We have, however, made adjustments to our patient management regimen based on the results of SAMMPRIS. This paper outlines our current patient selection, procedural technique, and post-procedure management. The complications we have encountered while developing our technique are described along with how to avoid them and how to manage them. Our most recent results (since previous publications) are also discussed.